Detection of aflatoxin M1 in human breast milk and raw cow's milk in Istanbul, Turkey - KARSLI, SEHER; KESKİN, YAŞAR (My University, 2009)
This survey was undertaken to determine the extent of aflatoxin M1 (AFM1) contamination in human breast milk and raw cow's milk in Istanbul, Turkey. Samples of human and raw cow's milk were collected randomly and analyzed for AFM1 using an enzyme-linked immunosorbent assay and high-performance liquid chromatography with fluorescence detection in which the samples were cleaned up with immunoaffinity columns. In this study, AFM, was detected in 8 (13.1%) of 61 human breast milk samples examined (mean +/- SD level, 5.68 +/- 0.62 ng/liter; range, 5.10 to 6.90 ng/liter) and 20 (33.3%) of 60 raw cow's milk samples examined (range, 5.40 to 300.20 ng/liter). Five (8.3%) of the positive raw cow's milk samples had AFM1 levels (153.52 +/- 100.60 ng/liter; range, 61.20 to 300.20 ng/liter) that were higher than the maximum tolerance limit (0.05 ppb) stipulated by regulations in Turkey and some other countries.
Keywords: Humans; Animals; Turkey; Cattle; Enzyme-Linked Immunosorbent Assay; Milk, Human; Chromatography, High Pressure Liquid; Aflatoxin M1; Milk